PENGARUH PENGGUNAAN EKSTRAK JAHE, KUNYIT DAN LENGKUAS SEBAGAI ADITIF PAKAN TERHADAP ANGKA MORTALITAS, BERAT KARKAS DAN BERAT LEMAK ABDOMINAL AYAM PEDAGING (GALLUS DOMESTICUS) - Siregar, Johan Erikson (Jurnal Sains Peternakan, 2014)
One aspect that has begun to replace antibiotic feed additives are studied as bioactive plant feed. Ginger, Turmeric and Galangal is a plant that is widely used in human life and are known to have a powerful substance that can also inhibit the growth of bacteria and fungi. Therefore, the use of ginger, turmeric and galangal in place antibiotic feed additives in poultry feed rations. Extracts of ginger, turmeric and galangal then mixed into a beverage with various doses of broiler chickens. Each dose level of 2%, 4%, 6%, 8%. Drinking water without the extract is also prepared for comparison. Extracts of ginger, turmeric and galangal given to broiler chickens aged 8 to 35 days, with 5 treatments and 4 replicates of each cage comprises 5 broiler chickens. The results showed that extracts of ginger, turmeric and galangal no significant effect (P<0.05) for mortality and carcass weights of abdominal fat weight while providing a significant effect (P>0.05).Keywords       :           Ginger, turmeric, galangal, Feed Additives, mortality rate, Carcass Weight, Weight and Abdominal Fat Broiler (Gallus domesticus)